Transformation of Students' Social Values in the Digital Era from the Perspective of Sociology of Education and Islamic Values - Hikma Fitriani; Nur Khasanah (Konsultan Jurnal Ilmiah Indonesia, 2025)
This research explores how students' social values have changed in the digital age by incorporating insights from educational sociology and Islamic moral principles. The concern arises from the increasing influence of online interactions, which modifies students' social conduct and disrupts the traditional ways in which values have been instilled by families, schools, and religious teachings. Through a qualitative, literaturebased method, the study reviews academic works related to digitalization, youth development, and Islamic ethical progress. The results indicate that online communication diminishes in-person interactions, fosters a focus on individuality, and promotes immediate gratification, leading to a reduced awareness of social norms. Educational institutions are becoming less effective as main socializing agents since digital platforms are taking control of students' activities, focus, and social influences. Nevertheless, organizations with strong moral foundations, particularly Islamic boarding schools, show more consistency in steering students' moral conduct because of their established routines, reinforcement of values, and community discipline. The analysis emphasizes that addressing the changes in values brought about by the digital era necessitates bolstering moral education, improving institutional roles, and ensuring that students' online behaviors align with Islamic moral standards.